The quadratic formula is given by:
x = (-b ± √(b^2 - 4ac)) / (2a)
In the given equation, a = -2, b = -7, and c = 13. Substituting these values into the quadratic formula, we have:
x = (-(-7) ± √((-7)^2 - 4(-2)(13))) / (2(-2))
x = (7 ± √(49 + 104)) / (-4)
x = (7 ± √(153)) / (-4)
Therefore, the solutions to the quadratic equation −2x^2−7x+13=0 are:
x = (7 + √153) / (-4)
x = (7 - √153) / (-4)
Solve the following quadratic equation using the quadratic formula. −2x^2−7x+13=0 show all your work
1 answer